2009
DOI: 10.4314/mejs.v1i2.46046
|View full text |Cite
|
Sign up to set email alerts
|

Screening Some Tef [Eragrostis Tef (Zucc.)Trotter] Accessions/Varieties for Salt Tolerance during Germination and Seedling Stage

Abstract: Salinity is a continuing problem in the arid and semi-arid tracts of the world. It could be alleviated using irrigation management and/or crop management. However, the former approach is outdated and very expensive. Nevertheless, the latter is economical as well as efficient, and it enables to produce salt tolerant crop lines. But prior to that there is a need to confirm the presence of genetic based variation for salt tolerance among different species or varieties of a particular crop that can thrive under un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Moreover, our results were in agreement with the findings of Abusuwar and Abbaker (2009), Asfaw and Itanna (2009) and Mamo et al (1996) who found that high levels of salinity can significantly inhibit seed germination in teff. In particular, increasing of salinity from 4 to 8 dS m -1 reduced the seed germination percentage and delayed germination time of various teff genotypes and no germination occurred in the highest salinity stress of 16 dS m -1 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, our results were in agreement with the findings of Abusuwar and Abbaker (2009), Asfaw and Itanna (2009) and Mamo et al (1996) who found that high levels of salinity can significantly inhibit seed germination in teff. In particular, increasing of salinity from 4 to 8 dS m -1 reduced the seed germination percentage and delayed germination time of various teff genotypes and no germination occurred in the highest salinity stress of 16 dS m -1 .…”
Section: Resultssupporting
confidence: 93%
“…There is evidence that teff shows moderate tolerance to salinity stress (Kebebew and McNeilly, 1995). However, relative data are rather inadequate (Mamo et al, 1996;Abusuwar and Abbaker, 2009;Asfaw and Itanna, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Over 11 million ha of land in Ethiopia are known to be salt affected (Ruffeis et al, 2008;Taddese, 2001). These salt-affected soils are prevalent in Rift Valley, the arid and semi-arid lowlands and other areas that are characterized by higher evapotranspiration rates (Asfaw and Itanna, 2009;Dubale, 2002;Geressu and Gezaghegne, 2008). To this effect, salinization has been a major constraint to the irrigated agriculture of the country.…”
Section: Salt Affected Soils and Salinitymentioning
confidence: 99%
“…For example, soil salinity has caused abandonment of banana plantation in Amibara, cotton plantation in Melka Sedi and nearly 30 ha of farmland in Metahara sugar plantation due to a progressive rise of groundwater as a result of over irrigation (Abebe et al, 2015;Abegaz, 1996;Ayenew, 2007). Asfaw and Itanna (2009) also indicates that of the entire Abaya State Farm, 30% has already been salt affected.…”
Section: Salt Affected Soils and Salinitymentioning
confidence: 99%
“…Since, India, China, and other sericulturally important countries have vast areas affected by salinity especially in the arid and semiarid regions, evolution of salt tolerant mulberry varieties are seen to be an essential part of the ongoing research. Although studies in other crops like barley (Kumar and Gupta, 1984), tef (Asfwa and Itanna, 2009) and wheat (El-Hendawy et al, 2009;Sinclair and Hoffmann, 2003) have shown that the magnitude of association among traits associated with plant growth and developments vary significantly under different growing conditions. Unfortunately, there is a fundamental gap in our understanding on the relationship between tolerance at low and high salinity levels in mulberry.…”
Section: Introductionmentioning
confidence: 99%